Time budgets and their uses - Andorka, Rudolf (1987)
The paper summarizes the state of the art of time budget survey and analyses. It firsts treats the new methodological developments, than reviews the different fields of utilization of time budget data; mass media contact, demand for cultural and other leisure goods and services, urban planning, consumer behavior, needs of elderly persons and of children, the sexual division of labor, the informal economy and household economics, social accounting, social indicators; quality of life, social structure. It deals also with the lessons from intertemporal and international comparisons of the results of time budget surveys.